PRACTICE OF DOCUMENT ASSEMBLY AND REASSEMBLY IN A SPECIALIZED AUTOMATED DOCUMENT CIRCULATION SYSTEM - KOROBEINIKOVA, TETIANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This work is dedicated to solving the problem of document assembly and reassembly during document circulation and focuses on the development of server-side algorithms. The work examines mechanisms that allow for reliable and unique digital signatures for documents by forming JWT tokens for actor identification and hashing documents using SHA256. Various organizations, especially educational ones, receive numerous requests in the form of documents that are manually formed, leading to an increase in bureaucratic errors. Thus, there is a need to analyze and improve methods and means of automated processing and generation of documents. The main focus is on the processes of document assembly and reassembly. The aim of the work is to develop and implement document circulation algorithms for creating and automated generation of documents in a specialized automated document circulation system (ADCS). This is achieved through the application of server procedures for document assembly and reassembly. ADCS is a document circulation system, the purpose of which is to automate the process of document processing and manual processes associated with them. The reassembly process is the breakdown of a document into separate parts, using special markers and regular expressions for further analysis of these parts. The assembly process involves converting a document from a program state to a physical one for further processing. During assembly, a document is formed using available program objects and data. Increasing the efficiency of document processing is achieved by leveling the shortcomings of the manual approach to document processing. A group of algorithms for the proposed ADCS is designed to improve the experience of using the services of institutions with high bureaucratic load.
Keywords: document circulation system; processes of document assembly and reassembly; document signing; digital signature; jwt token; hashing